東南極で進行中の大気-氷床-海洋システムの変動の観測と研究 - 平沢, 尚彦; プロジェクト, グループ; Naohiko, Hirasawa; Project, group (2013)
Any significant warming signals have not been detected for East Antarctic surface yet. However, recently, we have had a large amount of accumulation in Dronning Maud Land (DML), East Antarctica, suggesting some kinds of change start to be visible for us. Thus, the purpose of this project is to detect ongoing climatic change in DML and to understand the mechanism. In the phase IX of the Japanese Antarctic program (2016-2020), the project will focus on (1) moisture and aerosols transport systems working dominantly in summer season and (2) interaction in melting and heat exchange between the icesheet and ocean. To complete the aims of the project, we hope to carry on a persistent observation at Dome Fuji and to capture wide range for DML in future. 第4回極域科学シンポジウム 特別セッション：[S] 南極研究の将来展望―第Ⅸ期6か年計画策定に向けて 11月14日（木） 国立極地研究所 ２階大会議室 conference object